2007
DOI: 10.1002/glia.20536
|View full text |Cite
|
Sign up to set email alerts
|

α7β1 integrin is a receptor for laminin‐2 on Schwann cells

Abstract: The Schwann cell basal lamina acts as an organizer of peripheral nerve tissue and influences many aspects of cell behavior during development and regeneration. A principal component of the Schwann cell basal lamina is laminin-2. This study was undertaken to identify Schwann cell receptors for laminin-2. We found that among several Schwann cell integrins that can potentially interact with laminin-2, only alpha7beta1 bound to laminin-2-Sepharose. Dystroglycan, a non-integrin Schwann cell receptor for laminin-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…19,50 Several laminin receptors are present in mature SCs, but the b1 subfamily of integrins have been shown to play a key role in nerve regeneration, being necessary for SCs-axons interactions and myelination. [51][52][53][54] Consistent with previous studies on the primary role the b1 subfamily of integrin in axonal sorting, 51,52,54 blocking of b1 integrins did not significantly affect adhesion of neither stem cells nor DRGs, but dramatically reduced neurite outgrowth of DRGs alone on laminin, or of DRG in the presence of dASC without laminin coating. However, this effect was reversed when dASC were seeded on laminin, suggesting that laminin preconditioning of dASC can enhance the neurotrophic effect of dASC and also override b1 mediated effects on neurite outgrowth.…”
supporting
confidence: 82%
“…19,50 Several laminin receptors are present in mature SCs, but the b1 subfamily of integrins have been shown to play a key role in nerve regeneration, being necessary for SCs-axons interactions and myelination. [51][52][53][54] Consistent with previous studies on the primary role the b1 subfamily of integrin in axonal sorting, 51,52,54 blocking of b1 integrins did not significantly affect adhesion of neither stem cells nor DRGs, but dramatically reduced neurite outgrowth of DRGs alone on laminin, or of DRG in the presence of dASC without laminin coating. However, this effect was reversed when dASC were seeded on laminin, suggesting that laminin preconditioning of dASC can enhance the neurotrophic effect of dASC and also override b1 mediated effects on neurite outgrowth.…”
supporting
confidence: 82%
“…Indeed, as shown in Fig. 5, the subcellular distribution of one of the major laminin receptors of SC, dystroglycan (Chernousov et al, 2007;Scherer and Arroyo, 2002), closely resembles that of AHNAK. Thus, in nonconfluent cultures, both AHNAK, and the transmembrane b-dystroglycan chain are preferentially localized in thin, filopodia-like processes, but less abundant in lamellipodia.…”
Section: Analysis Of Potential Ahnak Function In Sc By Sirna Interfermentioning
confidence: 76%
“…It is known that laminin influences cellular behaviour via binding to cell surface receptors such as dystroglycan (Yamada et al, 1996) or integrins (Chernousov et al, 2007;Feltri et al, 2002); by contrast, the mechanisms underlying the observed effects of matrilin 2 are currently poorly understood. Except for matrilin 4, all matrilins mediate cell attachment, but the binding does not lead to the formation of focal contacts and reorganization of the actin cytoskeleton.…”
Section: Effects Of Matrilin 2 On Cell Migration and Axonal Outgrowthmentioning
confidence: 99%